Lagrange interpolation polynomial in a linear space with inner product - Kashpur, O.F.; Khlobystov, V.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
In a linear infinitedimensional space with inner product and in a finitedimensional Euclidean space, the accuracy of the Lagrange formula on polynomials of the corresponding degree is investigated.